2022
DOI: 10.1002/adbi.202200007
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin‐1‐Mediated SARS‐CoV‐2 Infection in Bone Marrow‐Derived Macrophages Inhibits Osteoclast Differentiation

Abstract: As of January 25, 2022, Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has caused more than 340 million infections with over 5.5 million deaths. [1] Coronavirus disease 2019 (COVID-19) patients may develop various clinical manifestations, including severe acute pulmonary disease, [2][3][4] hepatic dysfunction, [3,4] kidney injury, [4] heart damage, [3,4] gastrointestinal, [5] pancreatic symptoms, [6] and olfactory dysfunction. [7] However, due to the lagged, yet possibly long-lasting eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Many studies have focused on the impact of Omicron infection on musculoskeletal diseases [ 17 , 18 ]. Inflammation can influence bone remodeling, and researchers have reported that chronic obstructive pulmonary disease, asthma, and cystic fibrosis can disrupt bone metabolism and lead to pathological bone loss [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have focused on the impact of Omicron infection on musculoskeletal diseases [ 17 , 18 ]. Inflammation can influence bone remodeling, and researchers have reported that chronic obstructive pulmonary disease, asthma, and cystic fibrosis can disrupt bone metabolism and lead to pathological bone loss [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This bone loss may be caused by the accumulation of circulating proinflammatory cytokines and activated osteoclast differentiation. Gao et al [ 17 ] found that SARS-CoV-2 can also directly infect bone marrow macrophages through non-canonical receptor Nrp1 rather than through ACE2, which in turn inhibits their differentiation into osteoclasts. These studies suggest that SARS-CoV-2 has the potential to cause complications that so far have been neglected, suggesting that we will need to follow-up on patients with COVID-19 for a longer duration to determine the impact of the virus on target organs outside the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that alveolar epithelial cells are sensitive to SARS-CoV-2 and alveolar macrophages also suffer from the infection of SARS-CoV-2 [131,132]. In addition, MHV-A59 infects mouse bone marrow-derived macrophages (BMDMs) and peritoneal macrophages (PMs) [133], while neuropilin-1 (NRP1) mediates SARS-CoV-2 to infect mouse BMDMs [134]. Accordingly, the infection of coronavirus is closely related with ferroptosis, which may provide a new therapeutic target for the treatment of COVID-19.…”
Section: Staphylococcus Aureus Infectionmentioning
confidence: 99%
“…As of May 13, 2022, the SARS-CoV-2 outbreak has caused more than 519.9 million infections with over 6.3 million deaths [1] (https://www.worldometers.info/coronavirus). The SARS-CoV-2 infected or COVID-19 patients may develop various clinical manifestations,including severe acute pulmonary disease [2,3], heart damage [4], kidney injury [4], hepatic dysfunction [4], pancreatic symptoms [5], gastrointestinal [6] and olfactory dysfunction [7]. However, the impact of COVID-19 may have long-lasting effects on the physiological systems.…”
Section: Introductionmentioning
confidence: 99%